(untitled) (Web of Teachers: Inderscience Research, 2025)
This article explores the significance of communication skills in student activities and offers insights into how these skills can be developed. Effective communication is a cornerstone of success in both academic and personal realms. For students, the ability to express ideas clearly, listen actively, and collaborate with peers is essential not only for academic achievement but also for personal development. Involvement in student activities provides a unique platform for honing these communication skills, preparing students for future challenges in their careers and social lives.